Interatomic Coulombic decay in a He dimer: ab initio potential-energy curves and decay widths - Kolorenč, Přemysl; Kryzhevoi, Nikolai V.; Sisourat, Nicolas; Cederbaum, Lorenz S. (Physical review. A, Atomic, molecular, and optical physics, 2010)
The energy gained by either of the two helium atoms in a helium dimer through simultaneous ionization and excitation can be efficiently transferred to the other helium atom, which then ionizes. The respective relaxation process called interatomic Coulombic decay (ICD) is the subject of the present paper. Specifically, we are interested in ICD of the lowest of the ionized excited states, namely, the He+(n=2)He states, for which we calculated the relevant potential-energy curves and the interatomic decay widths.